Tailoring the electrical properties of multilayer MoS2 transistors using ultraviolet light irradiation1. Issue 94 (14th October 2015) - Singh, Arun Kumar; Andleeb, Shaista; Singh, Jai; Eom, Jonghwa
<x xml:space="preserve">Abstract</x> Modulating the electronic properties of MoS2 is essential in order to obtain the best performance of its electronic and optoelectronic devices as well as enabling fabrication of various complex devices.